2013
DOI: 10.1111/jdv.12236
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and predictions of cutaneous melanoma across Europe up to 2015

Abstract: Incidence rates of melanoma are expected to continue rising. These trends are worrying in terms of disease burden, particularly in eastern European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
3
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(180 citation statements)
references
References 33 publications
5
163
3
9
Order By: Relevance
“…To be eligible for assessment, websites had to meet the following inclusion criteria: (1) contain information on immunotherapy referring to melanoma, (2) contain at least 5 sentences of information, (3) be accessible for free and for all users (including patients and lay persons), (4) information is provided in German language. Websites were excluded if they were solely patient exchange platforms, advertising websites, conference or congress websites (e.g.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…To be eligible for assessment, websites had to meet the following inclusion criteria: (1) contain information on immunotherapy referring to melanoma, (2) contain at least 5 sentences of information, (3) be accessible for free and for all users (including patients and lay persons), (4) information is provided in German language. Websites were excluded if they were solely patient exchange platforms, advertising websites, conference or congress websites (e.g.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Melanoma incidence has been increasing worldwide [1,2]. In Germany, it accounts for about 4% of all cancers and is the fifth most common malignancy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous melanoma is a common malignant skin cancer and its incidence is increasing steeply [1]. Melanomas have a poor prognosis because they are highly invasive and metastasize rapidly; in addition, they are resistant to various conventional therapies.…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by two studies in Whites in Cape Town which showed an increase in incidence in both men and women when figures from 1990 to 1995 were compared with that from 2001 to 2003 (10,11). Reported data from all of South Africa indicate that the incidence in the White population is similar to that found in European countries (18) …”
Section: Incidence Of CM In the White And Black African Population Grmentioning
confidence: 86%